2021
DOI: 10.31486/toj.21.0026
|View full text |Cite
|
Sign up to set email alerts
|

First Trimester Mean Platelet Volume, Neutrophil to Lymphocyte Ratio, and Platelet to Lymphocyte Ratio Values Are Useful Markers for Predicting Preeclampsia

Abstract: Background: Preeclampsia complicates 2% to 8% of all pregnancies. Systemic inflammatory response (SIR) markers are widely used in the diagnosis of many inflammatory diseases and in the prediction of complicated pregnancies. This study examined the diagnostic value of SIR markers during the first trimester of pregnancy to predict preeclampsia development. Methods: This retrospective case-control study was conducted from January 2020 to May 2020. We included 94 patients diagnosed with mild preeclampsia, 107 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 39 publications
0
21
0
1
Order By: Relevance
“…The NLR was calculated by dividing the neutrophil count by the lymphocyte count. The PLR was calculated by dividing the platelet count by the lymphocyte count 19,20 . We used the neonatal data from birth until discharge.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NLR was calculated by dividing the neutrophil count by the lymphocyte count. The PLR was calculated by dividing the platelet count by the lymphocyte count 19,20 . We used the neonatal data from birth until discharge.…”
Section: Methodsmentioning
confidence: 99%
“…The PLR was calculated by dividing the platelet count by the lymphocyte count. 19,20 We used the neonatal data from birth until discharge. Neonatal data included the birth week, birth weight, intrauterine fetal demise, length of NICU stay, neonatal morbidity and mortality, and overall survival rate at discharge.…”
Section: Methodsmentioning
confidence: 99%
“…Advanced maternal age was diagnosed as pregnant women being 35 years or older at the delivery time 19 . Preeclampsia was identified as maternal hypertension >140/90 mmHg without a previous history of hypertension and 300 mg/L proteinuria without a history of renal disease 20,21 . GDM was diagnosed with a 75‐g oral glucose tolerance test (OGTT) between 24–28 weeks of gestation.…”
Section: Methodsmentioning
confidence: 99%
“…19 Preeclampsia was identified as maternal hypertension >140/90 mmHg without a previous history of hypertension and 300 mg/L proteinuria without a history of renal disease. 20,21 GDM was diagnosed with a 75-g oral glucose tolerance test (OGTT) between 24-28 weeks of gestation. The threshold values for fasting, 1-h, and 2-h plasma glucose concentrations were 92 mg/dL, 180 mg/dL, and 153 mg/dL, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Pregnancy comprises a unique immunological situation that is modulated since the immune system is affected by signals generated from the placenta. [12][13][14][15][16][17][18] Moreover, it was reported that pregnant women are predisposed to serious complications and death due to seasonal influenza epidemics compared to the general population. [19] This study aimed to report the experiences of our clinic on maternal deaths due to COVID-19.…”
Section: Introductionmentioning
confidence: 99%